Inflammation and Epidural-Related Maternal Fever: Proposed Mechanisms. (May 2016) - Sultan, Pervez; David, Anna L.; Fernando, Roshan; Ackland, Gareth L.
Abstract : Intrapartum fever is associated with excessive maternal interventions as well as higher neonatal morbidity. Epidural-related maternal fever (ERMF) contributes to the development of intrapartum fever. The mechanism(s) for ERMF has remained elusive. Here, we consider how inflammatory mechanisms may be modulated by local anesthetic agents and their relevance to ERMF. We also critically reappraise the clinical data with regard to emerging concepts that explain how anesthetic drug–induced metabolic dysfunction, with or without activation of the inflammasome, might trigger the release of nonpathogenic, inflammatory molecules (danger-associated molecular patterns) likely to underlie ERMF.